THE DEVELOPMENT MODEL OF REGIONAL MARKETING IN THE EXPERIENCE OF FOREIGN COUNTRIES (Marketing Journal, 2025)
This article explores the development and application of territorial marketing strategies based on international e xperience, with a focus on their implementation potential in Uzbekistan. The study employed content analysis and comparative methods using recent scholarly sources (Scopus, Web of Science) related to “territorial marketing”, “regional branding”, and “city marketing”. The results demonstrate that in developed countries, territorial marketing serves as a strategic tool for sustainable development and innovation, with active local community participation. The paper 43 proposes a conceptual framework and practical recommendations for implementing regional marketing in Uzbekistan through institutional collaboration and capacity - building.
Keywords: territorial marketing; regional brand; place image; regional competitiveness; city marketing; sustainable development; innovation strategy; international experience; local community; investment attractiveness